(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Current data on COVID-19 shows that hypertensive patients are the most vulnerable to this virus. These patients have low activation rates of the angiotensin-converting enzyme 2 (ACE2), and angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers (ARBs) are commonly used in the treatment of hypertension. Unfortunately ACE2 is the ideal receptor of the COVID-19 and this paradoxworries doctors. Our role in this modeling consist on leading the researchers towards a new concept and treatment based on the relationship between the activity of the Na / Ca exchanger (NCX) of the cardiac cell and the activation rate of ACE2. The results obtained of the INCX exchange current, the calcium transient and the action potential AP are very promising and show the direct effect of ACE2 on the exchanger which influences the cardiac electrical activity